2017
DOI: 10.22487/j24428744.0.v0.i0.8610
|View full text |Cite
|
Sign up to set email alerts
|

Review Hepatoprotektor Rosela (Hibiscus sabdariffa): Aktivitas, Mekanisme Aksi dan Toksisitas

Abstract: Liver cirrhosis has become a health problem in the world that caused mortality significantly. Treatment used herbs from various countries has been widely applied, one of them by consuming roselle (Hibiscus sabdariffa) calyx extract. This review will be discusse about the usage of H.sabdariffa calyx extract as hepatoprotectorwhich can inhibit the increasing of clinical parameters, such as ALT, AST, ALP, and LDH in various inducer, ie acetaminophen, CCl4, CdCl2, DNPH, and TAA. Its mechanism of action are as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Increased levels of SGPT and SGOT indicate acetaminophen-induced liver tissue toxicity. Selection of acetaminophen doses that can induce hepatotoxic events based on some scientific literature of similar hepatoprotector studies in rat test animals with minor modifications [26][27][28]. This finding is in line with Olaleye et al (2010) who reported that SGPT and SGOT are specific biochemical parameters for detecting liver damage or injury.…”
Section: Biochemical Resultssupporting
confidence: 62%
“…Increased levels of SGPT and SGOT indicate acetaminophen-induced liver tissue toxicity. Selection of acetaminophen doses that can induce hepatotoxic events based on some scientific literature of similar hepatoprotector studies in rat test animals with minor modifications [26][27][28]. This finding is in line with Olaleye et al (2010) who reported that SGPT and SGOT are specific biochemical parameters for detecting liver damage or injury.…”
Section: Biochemical Resultssupporting
confidence: 62%
“…This indicates that the food bar can protect the liver and reduce the release of SGPT and SGOT. The compounds with antioxidant properties in the extract can stabilize free radicals and prevent cell membrane damage [37].…”
Section: Sgpt and Sgot Enzyme Activitiesmentioning
confidence: 99%
“…8,9 A hepatoprotector is a substance that functions to protect the liver from damage while restoring damage to the liver. [1][2][3][4][5][6]10 Previous research results showed that various plants that have the property to maintain liver function, including Hibiscus sabdariffa 11 , Eurycoma longifolia Jack. 1 , and Pithecellobium lobatum Benth.…”
Section: Introductionmentioning
confidence: 99%